A Qualitative Study of Anxiety for Santri at the "Durrotu Ahlissunah Wal Jamaah Semarang" Islamic Boarding School in Facing the Covid-19 Pandemic - Zahid, Akhmad; Munawaroh, Eem (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
Anxiety is a normal symptom in humans. However, it will be called pathological if the symptoms persist and disturb the peace of the individual. Anxiety can occur as a result of a response to stress or conflict. The response is in the form of worry, anxiety, fear, and a sense of discomfort as a result of the threat of danger from inside and outside the individual. On March 11, 2020, the World Health Organization (WHO) declared the spread of COVID-19 to be categorized as a pandemic. This research is a descriptive study with qualitative methods. The research subjects were 5 students of the Durrotu Ahlissunah wal Jamaah Islamic Boarding School. The results showed that the students of the Durrotu Ahlissunah Wal Jamaah Islamic boarding school felt that there was no sense of feeling in the face of the ongoing Covid-19 conditions.